2006
DOI: 10.1136/jcp.2005.034280
|View full text |Cite
|
Sign up to set email alerts
|

Weight correction of MoM values: which method?

Abstract: Background: Adjusting maternal serum markers for maternal weight is considered to be a standard practice when screening for pregnancies associated with Down's syndrome. The choice of model for taking maternal weight into account is, however, rarely explicitly evaluated. Method: The relationship between the maternal serum markers afetoprotein (AFP), human chorionic gonadotropin (HCG) and unconjugated oestriol (uE3), determined with the Beckman Coulter access reagents and maternal weight was investigated in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 10 publications
0
14
0
3
Order By: Relevance
“…The main reason for the intolerably high false-positive rate for the biochemical trisomy 21 risk of PRC seems to be the fact that this software does not take into account maternal weight, nor are the so-called DoE values (that have been introduced instead of the internationally accepted MoM values) corrected for smoking, ethnicity, or IVF pregnancy status. Correction for maternal weight and ethnicity is generally regarded as essential in Down's syn- drome screening [12][13][14][15] , and the absence of a correction can lead to increased false-positive rates. Spencer et al [14] found that correction of the biochemical parameters for maternal weight resulted in a decrease in the falsepositive rate while maintaining the same detection rate.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for the intolerably high false-positive rate for the biochemical trisomy 21 risk of PRC seems to be the fact that this software does not take into account maternal weight, nor are the so-called DoE values (that have been introduced instead of the internationally accepted MoM values) corrected for smoking, ethnicity, or IVF pregnancy status. Correction for maternal weight and ethnicity is generally regarded as essential in Down's syn- drome screening [12][13][14][15] , and the absence of a correction can lead to increased false-positive rates. Spencer et al [14] found that correction of the biochemical parameters for maternal weight resulted in a decrease in the falsepositive rate while maintaining the same detection rate.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, marker levels were stated in terms of multiple of the median (MoM) and thus were standardized on the most important confounding factors: gestational age, tobacco use, weight, and diabetes mellitus. 5,[12][13][14] Therefore, to adjust for confounding factors not taken into account in the calculation of this standardized rate, we matched cases and controls on geographic origin and fetal sex. We adopted a second-trimester double test based on serum AFP and total hCG levels.…”
Section: Methodsmentioning
confidence: 99%
“…Çalışmamızda bölgemizdeki gebelerin nüfus kayıtlarının eksik olabildiği göz önüne alınarak formlar teslim alınırken gebenin gerçek doğum tarihi öğrenilip kaydedilmiştir. Bazı programlar gebenin ağırlığı olmadan da risk hesaplaması yapmaktadır, fakat gebenin ağırlığının düzeltme faktörü olarak kullanılıp hesaplanan risk analizleri daha güvenilirdir [17]. Bu yüzden çalışmamızda formlar laboratuvarda teslim alınırken eksik bilgiler kontrol edilmiş gebenin ağırlığı formda eksik ise tamamlanmıştır.…”
Section: Discussionunclassified